Univer-cities : strategic implications for Asia : readings from Cambridge and Berkeley, to Singapore - Carolin, Peter (World Scientific, 2013)
"Univer-cities : Strategic Implications for Asia aims to redefine the multi-faceted symbiotic relationship between universities and host cities. The four readings in this reader will invite readers to challenge the traditional view of what a university is as a place, and re-define the university as a space; drawing discoverers, creators, and seekers who are keen to preserve and enhance the value of higher education in Asia. The reader will also show how universities can make a huge and innovative impact on the immediate, surrounding, and global communities that are drawn into its ambit of its campus and sought out by the university in inter-univer-city and trans-disciplinary linkages"--